The End of Bordenkircher: Extending the Logic of Apprendi to Plea Bargaining - Michael M. O'Hear (Washington University Law Review, 2006)
Although the Supreme Court approved of the use of charging threats nearly thirty years ago in Bordenkircher v. Hayes, a more recent line of cases has subtly undermined key premises of that landmark decision. In order to induce guilty pleas, prosecutors might use any of a number of different tactics. A prosecutor might, for instance, charge aggressively in the first instance and then promise to drop the most serious charges in return for a guilty plea to a lesser offense. Bordenkircher v. Hayes addressed the mirror-image of this tactic: the prosecutor filed relatively minor charges at first, but then threatened to pursue more serious charges if the defendant did not plead guilty. The Supreme Court approved of such charging threats based on two considerations: the efficiency benefits of resolving cases by plea instead of jury trial, and the possibility that prosecutors would evade a ban on threats by charging more aggressively in the first instance. The Court’s reasoning, however, is inconsistent with Apprendi v. New Jersey and its progeny. Apprendi rejected the use of both efficiency considerations and evasion concerns as grounds for impairing access to juries. Apprendi instead emphasized a need for robust checks and balances within the criminal justice system. Because the Apprendi line of cases addressed sentencing procedures, not plea bargaining, their relevance to Bordenkircher v. Hayes has thus far escaped notice. The Article argues, however, that the Court should now overturn Bordenkircher v. Hayes in light of the values it embraced in Apprendi. The Article also proposes a new test for evaluating the constitutionality of charging threats.
Keywords: Plea bargaining; Sentences (Criminal procedure) – Enhancement; Burden of proof; Prosecution – Decision making; Apprendi v. New Jersey 530 U.S. 446 (2000); Borderkircher v. Hayes 434 U.S. 357 (1978)